Effects of Molecular Structure and Packing Order on the Stretchability of Semicrystalline Conjugated Poly(Tetrathienoacene‐diketopyrrolopyrrole) Polymers. (23rd December 2016) - Lu, Chien; Lee, Wen‐Ya; Gu, Xiaodan; Xu, Jie; Chou, Ho‐Hsiu; Yan, Hongping; Chiu, Yu‐Cheng; He, Mingqian; Matthews, James R; Niu, Weijun; Tok, Jeffery B.‐H.; Toney, Michael F.; et al.
Abstract : The design of polymer semiconductors possessing high charge transport performance, coupled with good ductility, remains a challenge. Understanding the distribution and behavior of both crystalline domains and amorphous regions in conjugated polymer films, upon an applied stress, shall provide general guiding principles to design stretchable organic semiconductors. Structure–property relationships (especially in both side chain and backbone engineering) are investigated for a series of poly(tetrathienoacene‐diketopyrrolopyrrole) polymers. It is observed that the fused thiophene diketopyrrolopyrrole‐based polymer, when incorporated with branched side chains and an additional thiophene spacer in the backbone, exhibits improved mechanical endurance and, in addition, does not show crack propagation until 40% strain. Furthermore, this polymer exhibits a hole mobility of 0.1 cm 2 V −1 s −1 even at 100% strain or after recovered from strain, which reveals prominent continuity and viscoelasticity of the polymer thin film. It is also observed that the molecular packing orientations (either edge‐on or face‐on) significantly affect the mechanical compliance of the polymer films. The improved stretchability of the polymers is attributed to both the presence of soft amorphous regions and the intrinsic packing arrangement of its crystalline domains. Abstract : Stretchable polymer electronics are regarded as the next generation of soft electronic devices. Structure–property relationships of conjugated poly(tetrathienoacene‐diketopyrrolopyrrole) polymers with molecular structure modification are demonstrated. The physical, electrical, and morphological properties of conjugated polymers are characterized to elucidate how the thin film behavior under various stretching conditions.